Pengembangan Virtual Tour 360 Photosphere untuk Meningkatkan Pengalaman Wisata Digital di Kabupaten Jembrana - I Wayan Arya Gina Widyatmaja; I Made Gede Sunarya; Subawa, I Gede Bendesa (Universitas Pendidikan Ganesha, 2024)
The virtual tour application using 360 photosphere in tourism in Jembrana Regency is designed to enhance the interest and digital experience of tourists or users to explore virtually without having to visit tourist sites directly. This research is motivated by the lack of effective promotional tools to increase tourist interest in visiting Jembrana Regency. This study employs a Research and Development method by applying the Multimedia Development Life Cycle development model, which involves the stages of Concept, Design, Material Collecting, Assembly, Testing, and Distribution. Based on the results from testing data on content expert evaluation, media expert evaluation, and effectiveness testing, a